2017
DOI: 10.1016/j.appet.2016.12.016
|View full text |Cite
|
Sign up to set email alerts
|

Is there an association between food patterns and life satisfaction among Norway's inhabitants ages 65 years and older?

Abstract: The lack of information regarding older adults' health and lifestyles makes it difficult to design suitable interventions for people at risk of developing unhealth lifestyles. Therefore, there is a need to increase knowledge about older adults' food patterns and quality of life. Our aim was to determine associations among food patterns, anxiety, depression, and life satisfaction in Norwegian inhabitants ages 65+. The Nord-Trøndelag Health Study (The HUNT Study) is a large, population-based cohort study that in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 37 publications
2
31
0
1
Order By: Relevance
“…These findings are similar to those of other European countries. 39,41 Our results showed that several unhealthy lifestyle behaviours appear to be more common in some regions of the Portugal (especially Azores and Madeira), suggesting that a combination of these modifiable risk factors might be present within specific groups of the population. Although we performed simple descriptive analysis in the current study, previous data including Portuguese adults of all ages suggested that some unhealthy lifestyle behaviours appear to be clustered in the same population groups.…”
Section: Health Characteristicsmentioning
confidence: 89%
See 1 more Smart Citation
“…These findings are similar to those of other European countries. 39,41 Our results showed that several unhealthy lifestyle behaviours appear to be more common in some regions of the Portugal (especially Azores and Madeira), suggesting that a combination of these modifiable risk factors might be present within specific groups of the population. Although we performed simple descriptive analysis in the current study, previous data including Portuguese adults of all ages suggested that some unhealthy lifestyle behaviours appear to be clustered in the same population groups.…”
Section: Health Characteristicsmentioning
confidence: 89%
“…Indeed, among the Norwegian population, a high proportion of participants reported 30 minutes or more of daily physical activity, with women achieving this level of activity more commonly than men (38.7% of women vs 33% of men). 41 The SENECA study showed significant variations in levels of physical activity among older adults across countries, ranging from 4% to 32%, with southern European countries having the lowest levels of activity. 39 Regarding dietary habits, a high proportion of Portuguese older adults reported daily intake of fruit and vegetables; however, the majority had inadequate water intake.…”
Section: Health Characteristicsmentioning
confidence: 99%
“…Then, we standardized these continuous food variables before running the K-means cluster analysis to make sure that food groups did not influence the clusters with specific frequency [31]. The result from the K-means cluster analyses resulted in two different diet patterns (healthy and unhealthy) which are already published [13]. We created the variable cohabitating by recoding elderly’s living situation into a dummy variable.…”
Section: Methodsmentioning
confidence: 99%
“…depressive symptoms) are associated with frailty. A healthy diet includes food types like fruits, vegetables, fish, whole-grain bread and water [13]. Thus, healthy diets also consist of food variety, enabling food components to be met adequately and comprehensively [14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation